Students' engagement with alternative discursive construction of menstruation. (October 2019) - Agnew, Shire; Gunn, Alexandra C
Objectives: Understandings of menstruation, including those within teaching, continue to draw on dominant discourses that construct menstruation as shameful and secret. This study trialled a new pedagogical approach to menstruation education that offered opportunities to engage with and mobilise alternative discourses. Design: Teachers of students (aged 10–12 years) in school years 7 to 8 were invited to participate in two workshops that used a critical literacy pedagogy to encourage learning about menstruation at schools. Classroom lessons were collaboratively planned. The teaching of the lessons was observed, and interviews with teachers and small groups of participating students were undertaken. Setting: South Island, New Zealand. Methods: Transcripts of workshops and interview data, in combination with field notes from the observed lessons, were subjected to discourse analysis. Results: Teachers still engaged with discourses of shame and secrecy in their work. Students, on the other hand, were observed to challenge discourses of shame and secrecy, and explored alternatives with which they could construct new meanings about menstruation. Conclusion: Findings suggest that it is important for teachers to examine personal constructions of menstruation. By approaching the teaching of menstruation in a way that offers space for students to engage with a variety of alternative discourses, teachers can help broaden the manner in which menstruation is understood.